An exploration around peer support for secondary pupils in Scotland with experience of self-harm. Issue 3 (2nd July 2020) - Shepherd, Victoria
ABSTRACT: Literature highlights friends as a main support for young people who self-harm, yet limited research explores specific supports offered by friends, or any help required to provide successful support. This research aimed to determine how friends support young people who self-harm; what friends could further do; and additional help needed to be a supportive friend. An interpretative phenomenological analysis approach was used to explore participants' lived experiences. Qualitative data were gathered from secondary pupils in Scotland via semi-structured interviews. Findings indicated that friends provide support by being directly there for young people, providing distractions and taking responsibility. Friends could consider young people's perspectives more, initiate conversations about self-harm and spend more time with young people. Supportive friends speak to others for reassurance and would like additional people to provide support. Implications for practice included highlighting support provided by friends, normalising the term 'self-harm' and providing peer support training for friends.